Klezmer : Music and Community in Twentieth-Century Jewish Philadelphia. - Netsky, Hankus (Temple University Press, 2015)
Klezmer presents a lively and detailed overview of the folk musical tradition as practiced in Philadelphia's twentieth-century Jewish community. Through interviews, archival research, and recordings, Hankus Netsky constructs an ethnographic portrait of Philadelphia's Jewish musicians, the environment they worked in, and the repertoire they performed at local Jewish lifestyle and communal celebrations.Netsky defines what klezmer music is, how it helped define Jewish immigrant culture in Philadelphia, and how its current revival has changed klezmer's meaning historically. Klezmer also addresses.